2018
DOI: 10.1007/s00253-018-9194-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of laboratory-scale bioreactors at the semi-continuous and continuous microbiological and biotechnological processes

Abstract: Laboratory-scale bioreactors represent an important part of microbiological, biotechnological, and biochemical researches. The small volume bioreactors enable the biomass growth, extracellular metabolite production, solid-state fermentation, and biocatalytic processes in a controlled open system. Using the lab-scale bioreactors, the processes which were optimized in experiments can be scaled up to a pilot level. In turn, the manufacturing scale processes can be scaled down to study the heterogeneity of the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…This is the first study to examine phage yield in a shake flask system and translate the process into a stirred tank bioreactor system. Developing the scaled down model was of critical importance as variable shake flask processes often lead to difficulties in achieving similar yields when the process is moved on into a stirred tank system (Garcia‐Ochoa & Gomez, ; Mitchell, Krieger, Stuart, & Pandey, ; Tikhomirova, Taraskevich, & Ponomarenko, ). The research presented here has shown that by narrowing the conditions used and focussing on those that positively influence phage infection, the titer achieved is reliable and validated at small scale and in a scale‐up system which focuses on larger volumes, automation, and controllable parameters, that is, pH and DO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to examine phage yield in a shake flask system and translate the process into a stirred tank bioreactor system. Developing the scaled down model was of critical importance as variable shake flask processes often lead to difficulties in achieving similar yields when the process is moved on into a stirred tank system (Garcia‐Ochoa & Gomez, ; Mitchell, Krieger, Stuart, & Pandey, ; Tikhomirova, Taraskevich, & Ponomarenko, ). The research presented here has shown that by narrowing the conditions used and focussing on those that positively influence phage infection, the titer achieved is reliable and validated at small scale and in a scale‐up system which focuses on larger volumes, automation, and controllable parameters, that is, pH and DO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This is the first study to examine phage yield in a shake flask system and translate the process into a stirred tank bioreactor system. Developing the scaled down model was of critical importance as variable shake flask processes often lead to difficulties in achieving similar yields when the process is moved on into a stirred tank system (Garcia-Ochoa & Gomez, 2009;Mitchell, Krieger, Stuart, & Pandey, 2000;Tikhomirova, Taraskevich, & Ponomarenko, 2018).…”
Section: Scale-upmentioning
confidence: 99%
“…Instead, a much better reproduction can be obtained at scale‐down simulators with longer circulation times. This suggests that the circulation time distribution plays a major role in the ultimate outcome and therefore population balances must be taken in account (Tikhomirova, Taraskevich, & Ponomarenko, ). Metabolomics analysis also suggests that losses of penicillin production did not show correlation with exposure to the substrate regimes (excess, limitation and starvation), but penicillin productivity showed an inverse relation with the intracellular glucose level (Wang, Zhao, et al, ).…”
Section: Quantitative Metabolomics and Its Application In Systems Metmentioning
confidence: 99%
“…Instead, a much better reproduction can be obtained at scale-down simulators with longer circulation times. This suggests that the circulation time distribution plays a major role in the ultimate outcome and therefore population balances must be taken in account (Tikhomirova, Taraskevich, & Ponomarenko, 2018).…”
Section: Metabolomics-assisted Systems Biology and Synthetic Biologmentioning
confidence: 99%
“…(Schmidt 2005 ). In contrast, semi-continuous and continuous processes can be operated in a reduced-sized bioreactor with good productivity (Tikhomirova et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%